Mental Health Expenditures: Association With Workplace Incivility and Bullying Among Hospital Patient Care Workers. Issue 8 (August 2018) - Sabbath, Erika L.; Williams, Jessica A.R.; Boden, Leslie I.; Tempesti, Tommaso; Wagner, Gregory R.; Hopcia, Karen; Hashimoto, Dean; Sorensen, Glorian
Abstract : Objective: Bullied workers have poor self-reported mental health; monetary costs of bullying exposure are unknown. We tested associations between bullying and health plan claims for mental health diagnoses. Methods: We used data from 793 hospital workers who answered questions about bullying in a survey and subscribed to the group health plan. We used two-part models to test associations between types of incivility/bullying and mental health expenditures. Results: Workers experiencing incivility or bullying had greater odds of any mental health claims. Among claimants, unexposed workers spent $792, those experiencing one type of incivility or bullying spent $1557 ( P for difference from unexposed = 0.016), those experiencing two types spent $928 ( P  = 0.503), and those experiencing three types spent $1446 ( P  = 0.040). Conclusion: Workplace incivility and bullying may carry monetary costs to employers, which could be controlled through work environment modification.